Why Do Women Using Intrauterine Contraceptive Devices? A Cross-Sectional Study - Misdayanti, Misdayanti; Damayanty, Sri; Ainurafiq, Ainurafiq; Handriani, Indah; Malik, Mayurni Firdayana; Herlina, Andi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Indonesia is one of the developing countries with the population being in the fourth position after China, India, and the United States. Therefore one of the efforts made by the government in suppressing the rate of population growth by Family Planning program. The purpose of this study was to analyze factors related to the use of Intrauterine Contraceptive (IUD) in the work area of Health Center Konda, Konawe Selatan Regional. This research applied analytic research with a cross-sectional design. The population as many as 3494 Couples of Childbearing Age and the sample amount to 72 respondents. Sampling technique using simple random sampling. The result showed that there is a correlation between knowledge with the use of contraception tool obtained p-value 0,026 <α = 0, 05, there is a correlation between attitude with contraception use obtained p-value 0.004 <α = 0, 05, there is a relationship between husband support with the use of contraception obtained p-value 0.000 <α = 0,05. This research concludes that there is a relationship between knowledge, attitude, and support of husband with the use of IUD in Work Area Health Center Konda of South Konawe Regency in 2017. The community, especially Couples of Childbearing Age, can actively increase knowledge about Intrauterine Contraceptive. Likewise, the Health Center especially midwives, should provide complete information about the Intrauterine Contraceptive, either directly or through banners.